Frozen elephant trunk in acute aortic type a dissection: risk analysis of concomitant root replacement. (4th February 2022) - Beckmann, Erik; Martens, Andreas; Kaufeld, Tim; Natanov, Ruslan; Krueger, Heike; Rudolph, Linda; Haverich, Axel; Shrestha, Malakh
Abstract: OBJECTIVES: To analyse whether full root replacement increases perioperative risks in patients who undergo frozen elephant trunk for acute aortic dissection. METHODS: Between March 2013 and December 2019, 115 patients underwent emergency frozen elephant trunk for acute dissection. Patients without root replacement were assigned to group A, while patients with concomitant full root replacement to group B. RESULTS: Mean age was 50.8 (12.5) years and 85 (73.9%) patients were male. Preoperative malperfusion was present in 49 (42.6%) patients. In group B, 27 (41.5%) patients received composite root replacement and 38 (33.0%) aortic valve-sparing David procedure. Cardiopulmonary-bypass and cross-clamp times were 252.5 (208.5–293.0) and 96.0 (40.5–148.0) min in group A, and 310.0 (274.0–346.5) and 121.0 (89.0–182.0) in group B ( P < 0.001). Continuous myocardial perfusion was used in 40 (80.0%) patients of group A and 59 (90.8%) of group B ( P = 0.098). Disabling stroke was present in 10 (20.0%) patients in group A and 12 (18.5%) in group B ( P = 0.835). Thirty-day mortality was 12.0% ( n = 6) in group A and 9.2% ( n = 6) in group B ( P = 0.630). The 1- and 5-year survival rates were 80% and 62% in group A, and 81% and 79% in group B. Logistic regression analysis identified age (odds ratio = 1.117, 95% confidence interval = 1.004–1.242, P = 0.041), cardiopulmonary-bypass time (odds ratio = 1.012, 95% confidence interval = 1.001–1.022, P = 0.029) and abdominal malperfusion (odds ratio = 17.394, 95% confidence interval = 2.030–149.013, P = 0.009) to be associated with 30-day mortality. CONCLUSIONS: Full root replacement does not increase the perioperative risk in patients who undergo frozen elephant trunk for acute dissection. Careful patient selection is important for such complex procedures. Continuous myocardial perfusion can help reducing the risk for intraoperative complications during such complex operations. Abstract : Total aortic arch replacement is a complex operative procedure and many patients require future aortic surgery [1].